RETRACTED: Background concentrations Hg in lakes Khanty-Mansi Autonomous Area, Russia - Zakharchenko A.V.; Tigeev A.A. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001